Pengaruh Terapi Musik Terhadap Penurunan Tingkat Depresi Pasien Stroke Non Hemoragik di RSUP N TB dan RSI Siti Hajar Mataram - Ainun Sajidah (STIKES Mataram, 2015)
Stroke is the loss of brainfunction caused by the cessation of blood supply to the brain. Stroke may be accompanied by depression as a comorbidity that can inhibit the healing process, so that needs to be handling. The purpose of this research is to determine the effect of music therapy to decrease levels of depression non hemorrhagic stroke patients. Design used in this study is Pra Experimental with one group pretest-posttest approach. The study population are all stroke patients who underwent treatment at RSUP Nusa Tenggara Barat and RSl Siti Hajar during the period of data collection. The samples Q/this study are non hemorrhagic stroke patients with awareness compos mentis and willing to become respondents. The number of samples is 21 people. The sampling technique is accidental sampling. Non hemorrhagic stroke patients are given treatment to listening to music twice a day in the morning and evening for 15 30 minutes within 1 week (7 days). Then evaluated after music therapy on day 7. Data collection using observation sheet to assess depression score from Depression Beck Inventory. The result of statistic analysis summarized that there are in?uence of music therapy to decrease levels of depression non hemorrhagic stroke patients (0 =0, OI, alpha =0, O5). Based on the result o/this study, recommended to policy makers to facilitate the provision of music therapy program at special care room of stroke patients so that they can do music therapy program simultaneously. And also, expected to nurse to motivate patients to actively participate to implement music therapy during treatment in hospital and at home. Keyword: Music therapy, depression, Non Haemorrhagic Stroke.